PROSPECTS OF USING ALTERNATIVE ENERGY SOURCES - VLASENKO, NATALIYA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Prospects for the use of environmentally friendly alternative energy sources are considered. Comparison of chemical and economic indicators in order to identify qualitative and quantitative differences. Among the considered alternative energy sources, solar batteries are the most promising. They are easy to use and maintain, affordable, durable, autonomous, provide full ecological safety in use and high reliability. In addition, the advantage is the renewable nature of solar panels (the speed of energy recovery is comparable to the speed of its depletion). Disadvantages include irregularity of supply, dependence on weather conditions, time of year and day. Amorphous (molten) silicon is used for the production of thin-film photocells, it is applied by spraying on various surfaces: polymer film, glass, plastic. Thin-film photocells based on cadmium telluride and indium-medigallium selenide, indium-copper selenide allow using many times less materials than for monocrystalline silicon, which makes them significantly cheaper.For solar panels of any type, it is necessary to take into account the angle of location, because when they are located at an angle of 60 °, approximately 55% of the lighting is lost during the day. The use of automated control systems that follow the sun and move the solar panels so that the sunlight falls perpendicular to the working surface allows to increase the amount of solar energy by 20-25%. By optimizing the composition and parameters of solar batteries (autonomous energy sources), it is possible to achieve significant results both from an economic and ecological point of view. The obtained results of parameters and composition of solar panels can be used for lighting private houses or commercial facilities.
Keywords: alternative sources of energy; renewable energy; solar panels; clean environment; resource conservation